Women’s Resilience in the Main Character of the Novel Hanauzumi - Nesa, Fakhria; Hawa, Andina Meutia (Universitas Andalas, 2025)
This study examines women’s resilience through the main character in Hanauzumi, a novel by Watanabe Jun’ichi. Employing a narrative approach and feminist literary criticism, the research explores the factors that shape resilience, the forms of resilience displayed by the female protagonist, Ogino Ginko, and the outcomes achieved. The findings reveal that both internal factors, such as trauma and illness, and external factors, including social pressures and societal expectations, shape Ginkgo’s resilience. In confronting these conditions, Ginkgo demonstrates strength through transformations in her appearance and her courage in facing social rejection. Ultimately, she succeeds in fulfilling her aspiration to become a female physician. The character Ogino Ginko in the novel Hanauzumi represents a resilient woman who can confront and overcome both internal pressures, such as trauma and illness, and external pressures in the form of social expectations and gender-based discrimination. The forms of resilience she demonstrates include symbolic identity transformation and the mental fortitude to persevere. Her ultimate achievement as a female physician signifies Ginko’s success in breaking through gender boundaries and proving that women are capable of determining their own life paths. This study highlights the importance of understanding the dynamics of women’s resilience in literary texts as a reflection of their existential struggle against patriarchal cultural dominance.